Prevalence and Factors Influencing Exclusive Breastfeeding Practice among Nursing Mothers - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Exclusive breastfeeding (EBF) is a key to achieving sustainable development goals (SDGs), but its practice has remained low in Nigeria, despite the strong evidences in support of EBF for the first six months of life.Setting and Design:This was a nine months descriptive cross-sectional study carried out among nursing mothers with children 6–24 months attending pediatric follow-up clinic and family health clinic of Usmanu Danfodiyo University Teaching Hospital, Sokoto.Materials and Methods:Interviewer administered questionnaire was used to obtain information on the sociodemographic characteristics and EBF practices of mothers.Statistical Analysis Used:Data were analyzed using SPSS version 20.Results:A total of 240 mothers were interviewed. The mean age of the mothers was 29.7 ± 6 years. All the respondents breastfed their children, 82 (34.2%) practiced EBF for six months. Higher level of maternal education (P= 0.001), ANC attendance (P= 0.001), maternal occupation (P= 0.007), hospital delivery (P= 0.007) significantly influence the practice of EBF for six months.Conclusion:EBF practice was sub optimal. Thus, improving utilization of antenatal care, female education, and hospital delivery are crucial interventions to increase EBF practice toward achieving SDG-2 and 3 in Sokoto.